2020
DOI: 10.1093/hmg/ddaa168
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic stress regulates genome-wide transcription in a PTEN-dependent manner

Abstract: PTEN is implicated in a wide variety of pathophysiological conditions and traditionally studied in the context of the PIK3-AKT–mTOR axis. Recent studies from our group and others have reported a novel role of PTEN in the regulation of transcription at the genome-wide scale. This emerging role of PTEN on global transcriptional regulation is providing a better understanding of various diseases, including cancer. Since cancer progression is an energy-demanding process and PTEN is known to regulate metabolic proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
1
0
0
Order By: Relevance
“…The response of cancer cells to glucose starvation has been extensively investigated by several previous studies, which highlighted multiple intrinsic mechanisms, in line with results of our study [ 53 57 ]. It is also important to underline that although here we focused on clones derived from established cancer cell lines, our group previously demonstrated that GDR/GDS populations exist also in OC patient-derived samples [ 58 ], thus underscoring the translational relevance of our findings.…”
Section: Discussionsupporting
confidence: 89%
“…The response of cancer cells to glucose starvation has been extensively investigated by several previous studies, which highlighted multiple intrinsic mechanisms, in line with results of our study [ 53 57 ]. It is also important to underline that although here we focused on clones derived from established cancer cell lines, our group previously demonstrated that GDR/GDS populations exist also in OC patient-derived samples [ 58 ], thus underscoring the translational relevance of our findings.…”
Section: Discussionsupporting
confidence: 89%